Nutrients condition in the rhizosphere of rubber tree (Hevea brasiliensis) - Wenbin Wang; Jianmel Geng; Xiaoping Wu; Yonghui Cao (Proceedings of IRRDB Conference: NR Industry: Responding to Globalization, 7-8 September 2004, Kunming International Convention & Exhibition Center, China. pp.138-143.)
Field experiment was carried out to study the nutrient condition in the rhizosphere of rubber tree (Hevea brasiliensis). The results showed that the treatments of various rates of fertilization had little effect on the nutrient condition in the rhizosphere and non-rhizosphere soils in a short time. In the 0~20cm layer, the contents of total N, total P and organic matter (O.M) were significantly (p<0.05 of P<0.01) higher in the rhizosphere than in the non-rhizosphere soils, respectively. The same was true for the contents of available N, P, K and exchangeable Ca, Mg as well as pH. In the 20-40cm layer, however, only the contents of total N, O.M., available N, available K and exchangeable Mg were significantly (p<0.05 or p<0.01) higher, respectively. Whether in the rhizosphere or the non-rhizosphere soils, the contents of O.M, available N, total N, total P and exchangeable Mg were all significantly (p<0.01) higher in 0~20cm layer than in 20-40cm layer, respectively. The reverse was true for pH. In non-rhizosphere soils, the content of available K in 0~20cm layer was significantly (p<0.01)higher than that in the 20-40cm layer. The content of exchangeable Ca was not significantly (p<0.05) different in the two layers of both rhizosphere and non-rhizosphere soils.
Keywords: Nutrient condition; Rhizosphere soils; Rubber tree